CContribution of the "Miriam Álvarez Brenes" Children's Library and the family in the formation of the reading habits of the children's population of University Gardens I and II, Heredia, Costa Rica: year 2007". - Jiménez Saballos, Yassir G. (2009)
This research is based on the "Contribution of the Miriam Álvarez Brenes Library and the family in the formation of the reading habits of the children of the community of Jardines Universitarios I and II in Heredia, by means of promotional activities, in the year 2007" The referred work is structured in five chapters that are distributed in the following way: The first chapter tackles and poses the problem to be solved, justifies the importance of the problem, and at the same time includes both general and specific objectives.In the second chapter the theoretical framework is developed; in the third chapter the procedures are developed. The analysis and presentation of the data is done in the fourth, using tables and graphs that support the findings of this research. The fifth and final chapter presents the recommendations and conclusions of the research work.